Pigmented villonodular synovitis mimics metastases on fluorine 18 fluorodeoxyglucose position emission tomography-computed tomography - Elumogo, Comfort O.; Kochenderfer, James N.; Civelek, A. Cahid; Bluemke, David A. (Quantitative Imaging in Medicine and Surgery; Vol 6, No 2 (April 28, 2016): Quantitative Imaging in Medicine and Surgery, 2016)
Pigmented villonodular synovitis (PVNS) is a benign joint disease best characterized on magnetic mesonance imaging (MRI). The role of fluorine 18 fluorodeoxyglucose (18F-FDG) position emission tomography-computed tomography (PET-CT) in the diagnosis or characterization remains unclear. PVNS displays as a focal FDG avid lesion, which can masquerade as a metastatic lesion, on PET-CET. We present a case of PVNS found on surveillance imaging of a lymphoma patient.